A method for preparing photocatalytic metal-organic framework composite fiber
By combining the metal organic frame complex (MOFS) with the polymer, and the introduction of AG nanoparticles in the fiber, the existing optical catalytic self -cleaning fiber material has a problem of low TIO2 visible light utilization rate and inorganic TIO2 particles in lack of accuracy , Achieve efficient self -cleaning effect and good mechanical properties.
Patent Information
- Application Number
- CN202211587990.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-09
AI Technical Summary
Among the existing photocatalytic self-cleaning fiber materials, the visible light utilization rate of TiO2 is low, and the fastness of the inorganic TiO2 particles to the fiber is insufficient, which affects the fiber feel and self-cleaning performance.
The metal organic framework complex (MOFS) is combined with polymer to prepare a high -performance photocatalytic metal organic frame complex fiber through the photocatalytic effect of MOFS and the assistance of AG nanoparticles. This method includes preparing MOFS products to mix together with polymers, prepare fiber through melting spinning wires or dry/wet spinning wires, and to form AG nanoparticles through AGNO3 and NABH4.
The efficient removal of fiber surface dust, organic matter and bacteria has a high self -cleaning effect, good wear resistance and durability, and at the same time solves the problem of easy reunion of pure MOFS materials, and improves the mechanical properties and flexibility of fiber.
Smart Images

Figure CN115807333B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fabric self-cleaning, and in particular relates to metal organic framework (MOFs) / polymer self-cleaning fabric and a preparation method thereof. Technical Background
[0002] With the increasing demand for functional fiber materials, fibers that not only have basic properties but also have environmentally friendly functions such as self-cleaning, antibacterial, and anti-pollution, the current self-cleaning coating technology is developing rapidly, especially self-cleaning fiber materials. Self-cleaning surfaces can be classified as hydrophobic or hydrophilic. The former can be achieved through chemical or geometric surface modification. The mechanism is to imitate the natural characteristics of the lotus leaf surface or butterfly wings, and the dust or debris attached to its hydrophobic surface can be removed by the rolling action of water droplets, and the cleanliness of the material can be maintained. However, most of these self-cleaning surface preparation methods require complex designs, sophisticated control technologies, or expensive hydrophobic materials such as fluorosilicone compounds. Hydrophilic self-cleaning, also known as the photocatalytic effect, is a chemical surface modification that uses photoactive substances to induce catalytic purification. Under the irradiation of light of a certain wavelength, the photocatalyst is stimulated to generate electron-hole pairs, in which electrons have strong reducing properties, while holes have oxidizing properties. Therefore, the photocatalyst has a strong oxidation-reduction effect in the presence of light, which can decompose many difficult-to-degrade organic substances, and destroy various dirt, stains, pollutants, or microorganisms on the surface of the photocatalyst through photooxidation and photoreduction reactions, inhibiting bacterial growth and viral activity, and achieving the purpose of self-cleaning. In addition, hydrophilic self-cleaning materials not only have self-cleaning functions, but also have additional properties such as antibacterial and deodorizing. Due to the huge potential of photocatalytic self-cleaning fiber materials in the global commercial market, the self-cleaning surface functionalization of fibers and fabrics has generally received more and more attention.
[0003] The structure of the fiber is prone to getting dirty and smelly, so it needs to be washed frequently to keep it clean. Studies have shown that the titanium dioxide coated surface has excellent antifouling and deodorizing properties due to its strong oxidation reaction, and is able to remove unpleasant odors such as sweat, shoe odor, car smoke, cigarette smoke and organic stains such as coffee, red wine and oil that cannot be effectively cleaned by laundry or dry cleaning. The fiber surface is also prone to breeding bacteria and affecting its use. Photocatalysts can decompose bacteria and mold spores attached to the fiber surface, and its mechanism is similar to antifouling and deodorization. Therefore, fiber materials with photocatalyst surface coating can act as a protective layer to prevent mold spores from growing on the fiber. On the other hand, fabrics are prone to deformation, distortion, pilling and other phenomena during washing, affecting their appearance, performance and general functions. Due to the self-cleaning function, damage caused by washing or distortion of clothing size triggers can avoid the reduction of washing cycles by simply exposing to light, helping to extend the service life of such materials. Self-cleaning fiber materials can be seen as one of the solutions to the simultaneous energy and resource crises. Because clothes or garments with automatic cleaning functions not only provide aesthetic advantages by maintaining their cleanliness, but also significantly reduce cleaning and maintenance costs by reducing the use of chemical detergents and the frequency of repeated washing. In addition, the time and electricity consumption required for the laundry process can be saved. Self-cleaning fiber materials provide economic and environmental benefits to our society. TiO2 has become a potential candidate material that exhibits photocatalytic activity and is widely used because of its non-toxicity, easy availability, cost-effectiveness, chemical stability and good physical and chemical properties. However, the low visible light utilization rate of TiO2 limits its application in the field of photocatalytic self-cleaning, and the inorganic TiO2 particles are not firmly bonded to the fiber, are easy to fall off, affect the fiber feel, and are difficult to disperse evenly on the fiber surface. Therefore, it is necessary to develop new photocatalytic self-cleaning materials that are suitable for fiber materials and have high performance.
[0004] Metal-organic frameworks (MOFs) are an emerging class of materials consisting of metal ions and organic linkers (ligands) held together by coordination bonds between metal ions / clusters and organic ligands (called secondary building units, SBUs). MOFs are promising candidates for bioremediation due to their chemical stability, rich porosity, and high surface area (up to 7000 m 2 g -1 ) has received increasing attention. When MOFs were first synthesized in the 1990s, they were initially used mainly for gas separation and storage. Later, MOFs were widely studied for other applications such as sensing, energy storage and conversion, drug delivery, photovoltaics, batteries, supercapacitors, fuel cells and catalysis. Since the past few years, MOFs have been further used in solar-driven applications, especially as photocatalysts for H2 evolution (via water decomposition), dye degradation, antibacterial and CO2 reduction. Therefore, the construction of photocatalytic self-cleaning fiber materials using MOFs and polymer fibers has potential application value. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of existing materials. The present invention provides a method for preparing metal organic framework composite fibers to solve the problems raised in the above-mentioned background technology. The preparation and application of the composite polymer fibers with self-cleaning properties of the present invention are of great significance to the development of the field of fiber self-cleaning.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a photocatalytic metal organic framework composite fiber, comprising the following steps:
[0008] Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A;
[0009] Step 2: dissolving the product A obtained in step 1 in a mixed solution of tetrahydrofuran and methanol, then adding a KOH aqueous solution, reflux the mixture, cool to room temperature, remove tetrahydrofuran and methanol by rotary evaporator, add additional water to the mixture until the solid is dissolved, then acidify the solution with acetic acid until no further precipitate is detected, collect the brown solid by filtration, wash with water and dry in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP);
[0010] Step 3: Prepare MOFs product by one of the following methods:
[0011] 3.a ZrCl4, 2-aminoterephthalic acid, TCPP, and benzoic acid were added to N, N-dimethylformamide in sequence, and then put into a reactor after ultrasonication. After the reaction, the reaction was cooled to room temperature, and the obtained product was washed with water and ethanol, and then vacuum dried to obtain a MOFs product;
[0012] 3.b: Titanium isopropoxide, 2-aminoterephthalic acid, and TCPP are added to a mixed solvent of N,N-dimethylformamide and ethanol in sequence, and then placed in a reactor after ultrasonic treatment. After the reaction, the mixture is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a MOFs product;
[0013] 3.c: AlCl3, 2-aminoterephthalic acid, and TCPP were added to a mixed solvent of N, N-dimethylformamide and deionized water in sequence, and then placed in a reactor after ultrasonic treatment. After the reaction, the mixture was cooled to room temperature, and the obtained product was washed with water and ethanol, and then vacuum dried to obtain the MOFs product;
[0014] Step 4: dissolving the polymer in a solvent, stirring at 20-80° C. for 6-24 hours to fully dissolve it, obtaining solution A, and then adding the MOFs product obtained in step 3 to solution A to obtain a mixed solution B, or mixing the polymer melt with the MOFs product to obtain a composite melt B, wherein the mixed solution B or the composite melt B is used as a spinning solution for standby use, wherein the mass fraction of the MOFs product is 5-70%;
[0015] Step 5: preparing composite fibers by melt spinning or dry / wet spinning or electrospinning;
[0016] Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / composite fiber, the obtained Ag + The composite fibers were immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag. + The Ag nanoparticles were obtained by reduction, and then washed with ethanol and dried to obtain AgNP / MOFs product / composite fibers.
[0017] The present invention also provides a method for preparing a photocatalytic metal organic framework composite fiber, comprising the following steps:
[0018] Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A;
[0019] Step 2: dissolving the product A obtained in step 1 in a mixed solution of tetrahydrofuran and methanol, then adding a KOH aqueous solution, reflux the mixture, cool to room temperature, remove tetrahydrofuran and methanol by rotary evaporator, add additional water to the mixture until the solid is dissolved, then acidify the solution with acetic acid until no further precipitate is detected, collect the brown solid by filtration, wash with water and dry in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP);
[0020] Step 3: dissolving the polymer in a solvent, stirring at 20-80°C for 6-24h to fully dissolve it, obtaining solution A, then adding ZrCl4 and benzoic acid to solution A, stirring at 20-80°C for 6-24h to fully mix them, obtaining a spinning solution for standby use, with a mass fraction of 2-10%;
[0021] Step 4: preparing Zr / polymer fibers by melt spinning or dry / wet spinning or electrospinning;
[0022] Step 5: Zr / polymer fiber, ZrCl4, 2.aminoterephthalic acid, TCPP, and benzoic acid are sequentially added to N,N-dimethylformamide, and then put into a reactor after ultrasonic treatment, and the MOFs product grows in situ on the fiber. After the reaction, the product is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a composite fiber;
[0023] Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / composite fiber, the obtained Ag + The composite fibers were immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag. + The Ag nanoparticles were obtained by reduction, and then washed with ethanol and dried to obtain AgNP / MOFs product / composite fibers.
[0024] In the above technical solution, in step 5:
[0025] Melt spinning: After the composite melt B is extruded through a screw and a spinneret, it is cooled to obtain a composite fiber;
[0026] Dry spinning: After the spinning solution is ejected from the spinneret, the solvent is evaporated in hot air to obtain composite fibers;
[0027] Wet spinning: The spinning solution is injected into a coagulation bath containing ethyl acetate, etc., and then vacuum filtered and dried to obtain composite fibers;
[0028] Electrospinning: Spinning was carried out with a spinneret of 0.6 mm in diameter at a flow rate of 1.5 mL / h, a high voltage of 15-20 kV was applied, and the distance between the collector and the spinneret was set to 15-20 cm. The fibers obtained were collected on a substrate (smooth silicone paper), and the temperature and relative humidity were maintained at 27 °C and 55%.
[0029] In the above technical solution, the polymer in step 4 is one or more of polyamide, polyacrylonitrile, cellulose xanthate, polyvinyl acetal, polyethyleneimine, polyether sulfone, and polyvinyl alcohol.
[0030] In the above technical scheme, the solvent in step 4 is one or more of: N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, toluene, acetone, tetrahydrofuran, chlorobenzene, dichloroethane, propylene oxide and epichlorohydrin.
[0031] In the above technical solution, the ratio of tetrahydrofuran to methanol in step 2 is 1:1-1:5, and the mass fraction of KOH is 0.5%-10%.
[0032] In the above technical scheme, it is characterized in that in step 6, the AgNO3 solution is a 5-40mM anhydrous ethanol solution; the NaBH4 solution is a 5-30mM anhydrous ethanol solution.
[0033] Because the present invention adopts the above technical solution, it has the following beneficial effects:
[0034] 1. The present invention mixes the AgNP / MOFs product into a polymer solution and prepares the fiber by melt spinning, dry spinning, electrostatic spinning or wet spinning. Pollutants such as dust, organic matter and bacteria adsorbed on the fiber surface can be removed by the photocatalytic action of AgNP / MOFs. Therefore, the fiber prepared by the present invention has the advantages of high self-cleaning effect, stable performance, good wear resistance, high durability, etc.
[0035] Second, the difficult-to-process powdered MOFs materials are combined with polymers through melt spinning, dry spinning, electrospinning or wet spinning to further process them into flexible materials, solving the problem of easy agglomeration of pure MOFs and giving polymer fibers efficient self-cleaning functions.
[0036] 3. The AgNPs / MOFs / composite fiber material provided by the present invention can be used as a self-supporting, self-cleaning flexible material without the need for additional binders, thereby solving the shortcoming of poor self-cleaning ability of flexible materials.
[0037] Fourth, the present invention provides two preparation methods. First, MOFs material is prepared first, and then the MOFs material and polymer are blended to form a spinning slurry, and then spinning is performed, wherein three types of MOFs materials are provided. Second, a metal salt solution and a polymer are first spun to form a metal salt / polymer precursor, and then the MOFs material is grown in situ. Both methods achieve the loading of MOFs on the polymer, so that the material has excellent mechanical properties and flexibility, and even during the folding process, good flexibility and stability are guaranteed.
[0038] Fifth, the present invention improves the visible light absorption performance of MOFs by introducing porphyrin ligands (TCPP), which greatly reduces the band gap energy, improves the photocatalytic quantum efficiency, and generates more photogenerated electron-hole pairs. Further, by introducing AgNPs, the separation of photogenerated electrons and holes is achieved, giving it excellent photocatalytic performance. The active oxygen free radicals generated under visible light further give the polymer fiber the ability to self-clean. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 SEM of AgNPs / MOFs product / polyacrylonitrile composite fibers with different mass fractions;
[0040] Figure 2Schematic diagram of the photocatalytic self-cleaning mechanism. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The present invention provides a method for preparing a photocatalytic metal organic framework composite fiber, comprising the following steps:
[0043] Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A;
[0044] Step 2: dissolving the product A obtained in step 1 in a mixed solution of tetrahydrofuran and methanol, then adding a KOH aqueous solution, reflux the mixture, cool to room temperature, remove tetrahydrofuran and methanol by rotary evaporator, add additional water to the mixture until the solid is dissolved, then acidify the solution with acetic acid until no further precipitate is detected, collect the brown solid by filtration, wash with water and dry in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP);
[0045] Step 3: Prepare MOFs product by one of the following methods:
[0046] 3.a ZrCl4, 2-aminoterephthalic acid, TCPP, and benzoic acid were added to N, N-dimethylformamide in sequence, and then put into a reactor after ultrasonication. After the reaction, the reaction was cooled to room temperature, and the obtained product was washed with water and ethanol, and then vacuum dried to obtain a MOFs product;
[0047] 3.b: Titanium isopropoxide, 2-aminoterephthalic acid, and TCPP are added to a mixed solvent of N,N-dimethylformamide and ethanol in sequence, and then placed in a reactor after ultrasonic treatment. After the reaction, the mixture is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a MOFs product;
[0048] 3.c: AlCl3, 2-aminoterephthalic acid, and TCPP were added to a mixed solvent of N, N-dimethylformamide and deionized water in sequence, and then placed in a reactor after ultrasonic treatment. After the reaction, the mixture was cooled to room temperature, and the obtained product was washed with water and ethanol, and then vacuum dried to obtain the MOFs product;
[0049] Step 4: dissolving the polymer in a solvent, stirring at 20-80° C. for 6-24 hours to fully dissolve it, obtaining solution A, and then adding the MOFs product obtained in step 3 to solution A to obtain a mixed solution B, or mixing the polymer melt with the MOFs product to obtain a composite melt B, wherein the mixed solution B or the composite melt B is used as a spinning solution for standby use, wherein the mass fraction of the MOFs product is 5-70%;
[0050] Step 5: preparing composite fibers by melt spinning or dry / wet spinning or electrospinning;
[0051] Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / MOFs product / composite fiber, the obtained Ag+ / composite fiber is immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag+ + The Ag nanoparticles were obtained by reduction, and then washed with ethanol and dried to obtain AgNP / MOFs product / composite fibers.
[0052] The present invention also provides a method for preparing a photocatalytic metal organic framework composite fiber, comprising the following steps:
[0053] Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A;
[0054] Step 2: dissolving the product A obtained in step 1 in a mixed solution of tetrahydrofuran and methanol, then adding a KOH aqueous solution, reflux the mixture, cool to room temperature, remove tetrahydrofuran and methanol by rotary evaporator, add additional water to the mixture until the solid is dissolved, then acidify the solution with acetic acid until no further precipitate is detected, collect the brown solid by filtration, wash with water and dry in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP);
[0055] Step 3: dissolving the polymer in a solvent, stirring at 20-80°C for 6-24h to fully dissolve it, obtaining solution A, then adding ZrCl4 and benzoic acid to solution A, stirring at 20-80°C for 6-24h to fully mix them, obtaining a spinning solution for standby use, with a mass fraction of 2-10%;
[0056] Step 4: preparing Zr / polymer fibers by melt spinning or dry / wet spinning or electrospinning;
[0057] Step 5: Zr / polymer fiber, ZrCl4, 2-aminoterephthalic acid, TCPP, and benzoic acid are sequentially added to N,N-dimethylformamide, and then ultrasonically placed in a reactor, and the MOFs product grows in situ on the fiber. After the reaction, the product is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a composite fiber;
[0058] Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / MOFs product / composite fiber, the obtained Ag + The / MOFs product / composite fiber was immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag. + The Ag nanoparticles were obtained by reduction, and then washed with ethanol and dried to obtain AgNP / MOFs product / composite fibers.
[0059] In the above technical solution, in step 5:
[0060] Melt spinning: After the composite melt B is extruded through a screw and a spinneret, it is cooled to obtain a composite fiber;
[0061] Dry spinning: After the spinning solution is ejected from the spinneret, the solvent is evaporated in hot air to obtain composite fibers;
[0062] Wet spinning: The spinning solution is injected into a coagulation bath containing ethyl acetate, etc., and then vacuum filtered and dried to obtain composite fibers;
[0063] Electrospinning: Spinning was carried out with a spinneret of 0.6 mm in diameter at a flow rate of 1.5 mL / h, a high voltage of 15-20 kV was applied, and the distance between the collector and the spinneret was set to 15-20 cm. The fibers obtained were collected on a substrate (smooth silicone paper), and the temperature and relative humidity were maintained at 27 °C and 55%.
[0064] In the above technical solution, the polymer in step 4 is one or more of polyamide, polyacrylonitrile, cellulose xanthate, polyvinyl acetal, polyethyleneimine, polyether sulfone, and polyvinyl alcohol.
[0065] In the above technical scheme, the solvent in step 4 is one or more of: N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, toluene, acetone, tetrahydrofuran, chlorobenzene, dichloroethane, propylene oxide and epichlorohydrin.
[0066] In the above technical solution, the ratio of tetrahydrofuran to methanol in step 2 is 1:1-1:5, and the mass fraction of KOH is 0.5%-10%.
[0067] In the above technical scheme, it is characterized in that in step 6, the AgNO3 solution is a 5-40mM anhydrous ethanol solution; the NaBH4 solution is a 5-30mM anhydrous ethanol solution.
[0068] Example 1
[0069] Step 1: Add 8 g of methyl p-formylbenzoate and 100 mL of propionic acid into a three-necked flask. Heat the mixture to 122°C and stir for 2 h. Then add 3 mL of pyrrole dropwise over 30 minutes. Reflux the solution for 12 hours. After cooling to room temperature, filter to obtain a purple solid. Wash the product with water and ethanol. Then vacuum dry for 8 hours to obtain product A.
[0070] Step 2: 1.8 g of the product A obtained in step 1 was dissolved in a mixed solution of 45 mL of tetrahydrofuran and 45 mL of methanol, and then 45 mL of a 10% aqueous solution of KOH was added. The mixture was refluxed at 70°C for 24 h. After cooling to room temperature, tetrahydrofuran and methanol were removed by rotary evaporator. Additional water was added to the mixture until the solid dissolved. The solution was then acidified with acetic acid until no further precipitate was detected. The brown solid was collected by filtration, washed with water and dried under vacuum to obtain compound B (TCPP).
[0071] Step 3: 0.3 g of ZrCl4, 0.3 g of 2-aminoterephthalic acid, 0.1 g of TCPP, and 5 g of benzoic acid were added to 20 mL of N, N-dimethylformamide in sequence, and then ultrasonicated for 10 min and placed in a reactor, reacted at 120 ° C for 12 h, and cooled to room temperature. The obtained product was washed with water and ethanol 5 times, and then vacuum dried at 80 ° C for 8 h to obtain MOFs product 1.
[0072] Step 4: Dissolve polyacrylonitrile in N,N-dimethylformamide, wherein the mass fraction of polyacrylonitrile is 15%, and stir at 75°C for 24 hours to fully dissolve it to obtain solution A. Then add the MOFs product 1 (mass fraction is 8%) obtained in step 2 to solution A. Then stir the obtained mixed solution B at 75°C for 24 hours to fully mix it, and obtain a spinning solution for use.
[0073] Step 5, then put 10 mL of solution B into a syringe and spin it under the conditions of 10 KV voltage, 25° C., and 10% relative humidity, with the distance between the syringe needle tip and the receiving plate being 5 cm, to obtain MOFs product 1 / polyacrylonitrile nanofibers.
[0074] Step 6: The MOFs product 1 / polyacrylonitrile fiber was immersed in an anhydrous ethanol solution with a molar concentration of AgNO3 of 18 mM for 24 h to obtain Ag + / MOFs product 1 / polymer fiber. The obtained Ag + / MOFs product 1 / polymer fiber was immersed in ethanol for solvent exchange 5 times, and then Ag + / MOFs product 1 / The polymer fiber was immersed in 20 mM NaBH4 anhydrous ethanol solution for 10 min to + The Ag nanoparticles were reduced and then washed with ethanol for 5 times and then dried under vacuum at 80°C for 6 h to obtain AgNPs / MOFs product 1 / polyacrylonitrile composite fibers.
[0075] Example 2
[0076] The sample preparation steps are the same as those in Example 1, wherein polyamide or polyacrylonitrile or cellulose xanthate or polyvinyl acetal or polyethylene imine or polyether sulfone or polyvinyl alcohol is used instead of polyacrylonitrile to obtain AgNPs / MOFs product 1 / polyamide composite fiber, AgNPs / MOFs product 1 / cellulose xanthate composite fiber, AgNPs / MOFs product 1 / polyvinyl acetal composite fiber, AgNPs / MOFs product 1 / polyethylene imine composite fiber, AgNPs / MOFs product 1 / polyether sulfone composite fiber, and AgNPs / MOFs product 1 / polyvinyl alcohol composite fiber, respectively.
[0077] Example 3
[0078] Step 1: Same as step 1 required in Example 1;
[0079] Step 2: Same as step 2 required in Example 1;
[0080] Step 3: Add 2.86 mL of titanium isopropoxide, 2.86 g of 2-aminoterephthalic acid, and 0.2 g of TCPP to a mixed solvent of 40 mL of N,N-dimethylformamide and 10 mL of ethanol in sequence, then put into a reactor after ultrasonic treatment for 10 min, react at 110 ° C for 72 h, cool to room temperature, wash the product with water and ethanol, and then vacuum dry to obtain MOFs product 2.
[0081] Step 4: The same as step 4 required in Example 1, wherein MOFs product 2 is used instead of MOFs product 1:
[0082] Step 5: The same as step 5 required in Example 1, wherein MOFs product 2 is used instead of MOFs product 1.
[0083] Step 6: The same as step 6 required in Example 1, wherein MOFs product 2 is used instead of MOFs product 1.
[0084] The obtained composite fiber has improved photocatalytic efficiency and can achieve self-cleaning effect under weaker visible light irradiation.
[0085] Example 4
[0086] The sample preparation steps are the same as those in Example 1, wherein polyamide or polyacrylonitrile or cellulose xanthate or polyvinyl acetal or polyethylene imine or polyether sulfone or polyvinyl alcohol is used instead of polyacrylonitrile to obtain AgNPs / MOFs product 2 / polyamide composite fiber, AgNPs / MOFs product 2 / cellulose xanthate composite fiber, AgNPs / MOFs product 2 / polyvinyl acetal composite fiber, AgNPs / MOFs product 2 / polyethylene imine composite fiber, AgNPs / MOFs product 2 / polyether sulfone composite fiber, and AgNPs / MOFs product 2 / polyvinyl alcohol composite fiber, respectively.
[0087] Example 5
[0088] Step 1: Same as step 1 required in Example 1;
[0089] Step 2: Same as step 2 required in Example 1;
[0090] Step 3: 3.94 g of AlCl3·6H2O, 3 g of 2-aminoterephthalic acid, and 0.2 g of TCPP were added in sequence to a mixed solvent of 4 mL of N,N-dimethylformamide and 36 mL of deionized water, and then ultrasonicated for 10 min and put into a reactor, reacted at 150 ° C for 5 h, cooled to room temperature, and the obtained product was washed with water and ethanol, and then vacuum dried to obtain MOFs product 3.
[0091] Step 4: The same as step 4 required in Example 1, wherein MOFs product 3 is used instead of MOFs product 1:
[0092] Step 5: The same as step 5 required in Example 1, wherein MOFs product 1 is replaced by MOFs product 3.
[0093] Step 6: The same as step 6 required in Example 1, wherein MOFs product 1 is replaced by MOFs product 3.
[0094] The photocatalytic efficiency of the obtained composite fiber is between that of the composite fiber with MOFs product 1 and MOFs product 2 added.
[0095] Example 6
[0096] The sample preparation steps are the same as those in Example 1, wherein polyamide or polyacrylonitrile or cellulose xanthate or polyvinyl acetal or polyethylene imine or polyether sulfone or polyvinyl alcohol is used instead of polyacrylonitrile to obtain AgNPs / MOFs product 3 / polyamide composite fiber, AgNPs / MOFs product 3 / cellulose xanthate composite fiber, AgNPs / MOFs product 3 / polyvinyl acetal composite fiber, AgNPs / MOFs product 3 / polyethylene imine composite fiber, AgNPs / MOFs product 3 / polyether sulfone composite fiber, and AgNPs / MOFs product 3 / polyvinyl alcohol composite fiber, respectively.
[0097] Example 7
[0098] Step 1: Same as step 1 required in Example 1.
[0099] Step 2: Same as step 2 required in Example 1.
[0100] Step 3: Dissolve polyacrylonitrile in N,N-dimethylformamide, wherein the mass fraction of polyacrylonitrile is 15%, and stir at 75°C for 24 hours to fully dissolve it to obtain solution A. Then add ZrCl4 (mass fraction 5%) and benzoic acid (mass fraction 20%) to solution A. Then stir the obtained mixed solution B at 75°C for 24 hours to fully mix it.
[0101] Step 4: Then 10 mL of solution B was placed in a syringe and spun at 10 KV voltage, 25° C., and 10% relative humidity. The distance between the syringe needle tip and the receiving plate was 5 cm to obtain Zr / polyacrylonitrile nanofibers.
[0102] Step 5: 0.3g ZrCl4, 0.3g 2-aminoterephthalic acid, 0.1g TCPP, and 5g benzoic acid were added to 20mL N,N-dimethylformamide to obtain a mixed solution C. Then the Zr / polyacrylonitrile fiber obtained in step 2 was immersed in the mixed solution C, and then ultrasonicated for 10min and placed in a reactor, reacted at 120°C for 12h, and MOFs product 1 grew in situ on the fiber, and cooled to room temperature. The obtained composite fiber was washed with water and ethanol, and then vacuum dried to obtain MOFs product 1 / polyacrylonitrile composite fiber.
[0103] Step 6: Same as step 6 of Example 1, obtaining AgNPs / MOFs product 1 / polyacrylonitrile composite fiber.
[0104] Example 8
[0105] The sample preparation steps are the same as those in Example 1, wherein polyamide or polyacrylonitrile or cellulose xanthate or polyvinyl acetal or polyethylene imine or polyether sulfone or polyvinyl alcohol is used instead of polyacrylonitrile to obtain AgNPs / MOFs product 1 / polyamide composite fiber, AgNPs / MOFs product 1 / cellulose xanthate fiber composite, AgNPs / MOFs product 1 / polyvinyl acetal composite fiber, AgNPs / MOFs product 1 / polyethylene imine composite fiber, AgNPs / MOFs product 1 / polyether sulfone composite fiber, and AgNPs / MOFs product 1 / polyvinyl alcohol composite fiber, respectively.
[0106] Example 9
[0107] The sample preparation steps are the same as those in Example 1-8, wherein electrospinning can be replaced by wet spinning. The spinning solution is injected into a coagulation bath containing ethyl acetate, etc. After vacuum filtration and drying, MOFs / polymer fibers are obtained.
[0108] from Figure 2 It can be seen that under visible light, MOFs absorb visible light, and electrons will jump from the valence band of the MOFs material to the conduction band, leaving holes (h+) and electrons (e+) in the valence band and conduction band respectively. - ), these h + and empty - It will combine with H2O or O2 to form hydroxyl radicals (·OH) or peroxyl radicals (·O2 - ). On the other hand, AgNPs loaded on MOFs can become e - transfer site, further increasing h + and e - The separation effect of the polymer fibers can generate more free radicals, which can degrade harmful pollutants and realize the self-cleaning of polymer fibers.
Claims
1. A method for preparing a photocatalytic metal organic framework composite fiber, characterized in that: The following steps are involved: Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A; Step 2: The product A obtained in step 1 is dissolved in a mixed solution of tetrahydrofuran and methanol, and then a KOH aqueous solution is added, the mixture is refluxed, and after cooling to room temperature, tetrahydrofuran and methanol are removed by a rotary evaporator, additional water is added to the mixture until the solid is dissolved, and then the solution is acidified with acetic acid until no further precipitate is detected, and the brown solid is collected by filtration, washed with water and dried in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP); Step 3: Prepare MOFs product by one of the following methods: Step 3.a: ZrCl4, 2-aminoterephthalic acid, TCPP and benzoic acid are added to N,N-dimethylformamide in sequence, and then put into a reactor after ultrasonic treatment. After the reaction, the reaction is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a MOFs product; Step 3.b: titanium isopropoxide, 2-aminoterephthalic acid, and TCPP are sequentially added to a mixed solvent of N,N-dimethylformamide and ethanol, and then placed in a reactor after ultrasonication. After the reaction, the reaction is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a MOFs product; Step 3.c: AlCl3, 2-aminoterephthalic acid, and TCPP are sequentially added to a mixed solvent of N,N-dimethylformamide and deionized water, and then placed in a reactor after ultrasonic treatment. After the reaction, the mixture is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a MOFs product; Step 4: dissolving the polymer in a solvent, stirring at 20-80° C. for 6-24 hours to fully dissolve it, obtaining solution A, and then adding the MOFs product obtained in step 3 to solution A to obtain a mixed solution B, or mixing the polymer melt with the MOFs product to obtain a composite melt B, and the mixed solution B or the composite melt B is used as a spinning solution for standby use, wherein the mass fraction of the MOFs product is 5-70%; Step 5: preparing composite fibers by melt spinning or dry / wet spinning or electrospinning; Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / composite fiber, the obtained Ag + The composite fibers were immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag. + The Ag nanoparticles were reduced and then washed with ethanol and dried to obtain AgNP / MOFs / composite fibers.
2. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 1, characterized in that: In step 5: Melt spinning: After the composite melt B is extruded through a screw and a spinneret, it is cooled to obtain a composite fiber; Dry spinning: After the spinning solution is ejected from the spinneret, the solvent is evaporated in hot air to obtain composite fibers; Wet spinning: The spinning solution is injected into a coagulation bath containing ethyl acetate, and then vacuum filtered and dried to obtain composite fibers; Electrospinning: Spinning was carried out with a spinneret of 0.6 mm in diameter at a flow rate of 1.5 mL / h, a high voltage of 15–20 kV was applied, and the distance between the collector and the spinneret was set to 15–20 cm. The fibers obtained were collected on a substrate, and the temperature and relative humidity were maintained at 27 °C and 55%.
3. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 1, characterized in that: The polymer in step 4 is one or more of polyamide, polyacrylonitrile, cellulose xanthate, polyvinyl acetal, polyethyleneimine, polyether sulfone, and polyvinyl alcohol.
4. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 3, characterized in that: The solvent in step 4 is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, toluene, acetone, tetrahydrofuran, chlorobenzene, ethylene dichloride, propylene oxide and epichlorohydrin.
5. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 4, characterized in that: The ratio of tetrahydrofuran to methanol in step 2 is 1:1-1:5, and the mass fraction of KOH is 0.5%-10%.
6. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 5, characterized in that In step 6, the AgNO3 solution is a 5-40 mM anhydrous ethanol solution; the NaBH4 solution is a 5-30 mM anhydrous ethanol solution.
7. A method for preparing a photocatalytic metal organic framework composite fiber, characterized in that: The following steps are involved: Step 1: methyl paraformylbenzoate and propionic acid are mixed to obtain a mixture, the mixture is heated to 80-160° C., stirred for 1-3 hours, and then pyrrole is added dropwise. After the solution is refluxed at 60-160° C. and cooled to room temperature, a purple solid is filtered to obtain the purple solid. The purple solid is washed with water and ethanol, and then dried in vacuo at 40-80° C. to obtain product A; Step 2: The product A obtained in step 1 is dissolved in a mixed solution of tetrahydrofuran and methanol, and then a KOH aqueous solution is added, the mixture is refluxed, and after cooling to room temperature, tetrahydrofuran and methanol are removed by a rotary evaporator, additional water is added to the mixture until the solid is dissolved, and then the solution is acidified with acetic acid until no further precipitate is detected, and the brown solid is collected by filtration, washed with water and dried in vacuo to obtain the compound meso-tetrakis(4-carboxyphenyl)porphyrin (TCPP); Step 3: dissolving the polymer in a solvent, stirring at 20-80°C for 6-24h to fully dissolve it, obtaining solution A, then adding ZrCl4 and benzoic acid to solution A, stirring at 20-80°C for 6-24h to fully mix them, obtaining a spinning solution for standby use, with a mass fraction of 2-10%; Step 4: preparing Zr / polymer fibers by melt spinning or dry / wet spinning or electrospinning; Step 5: Zr / polymer fiber, ZrCl4, 2-aminoterephthalic acid, TCPP, and benzoic acid are sequentially added to N,N-dimethylformamide, and then ultrasonically placed in a reactor, and the MOFs product grows in situ on the fiber. After the reaction, the product is cooled to room temperature, and the obtained product is washed with water and ethanol, and then vacuum dried to obtain a composite fiber; Step 6: The composite fiber is immersed in AgNO3 solution to obtain Ag + / composite fiber, the obtained Ag + The composite fibers were immersed in ethanol for solvent exchange 3-5 times, and then immersed in NaBH4 solution to remove Ag. + The Ag nanoparticles were reduced and then washed with ethanol and dried to obtain AgNP / MOFs products / composite fibers.
8. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 7, characterized in that: The polymer in step 4 is one or more of polyamide, polyacrylonitrile, cellulose xanthate, polyvinyl acetal, polyethyleneimine, polyether sulfone, and polyvinyl alcohol; The solvent in step 4 is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, toluene, acetone, tetrahydrofuran, chlorobenzene, ethylene dichloride, propylene oxide and epichlorohydrin.
9. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 7, characterized in that: The ratio of tetrahydrofuran to methanol in step 2 is 1:1-1:5, and the mass fraction of KOH is 0.5%-10%.
10. The method for preparing a photocatalytic metal organic framework composite fiber according to claim 7, characterized in that In step 6, the AgNO3 solution is a 5-40 mM anhydrous ethanol solution; the NaBH4 solution is a 5-30 mM anhydrous ethanol solution.
Citation Information
Patent Citations
Preparation method and application of fiber composite membrane catalyst
CN108940374A
Preparation method and antibacterial application of photosensitive semiconductor Zr-TCPP MOFs loaded Ag nano particle composite material
CN111110843A
Preparation method and application of porphyrin-metal organic framework material
CN111804341A